Effect of Zirconium on the Densification of Reactively Hot‐Pressed Zirconium Carbide. Issue 10 (24th July 2014) - Chakrabarti, Tamoghna; Rangaraj, Lingappa; Jayaram, Vikram; Fahrenholtz, W.
<x xml:space="preserve">Abstract</x> Densification mechanisms involved during reactive hot pressing (RHP) of zirconium carbide (ZrC) have been studied. RHP has been carried out using zirconium (Zr) and graphite (C) powders in the molar ratios 1:0.5, 1:0.67, 1:0.8, and 1:1 at 40 MPa, 800°C–1200°C for different durations. The volume fractions of phases formed, including porosity, are determined from the measured density and from Rietveld analysis. Increased densification with an increasing nonstoichiometry in carbon has been observed. Microstructural and X‐ray diffraction observations coupled with the predictions of a model based on the constitutive laws governing plastic flow of zirconium suggest that the better densification of nonstoichiometric compositions arise from the higher amount of starting Zr and also the longer duration of its availability for plastic flow during RHP. Volume shrinkage due to reaction between Zr and C and the gradual elimination of the soft metal phase limit the final density achievable. Based on these observations, a two‐step RHP carried out at 800°C and 1200°C leads to a better densification than a single RHP at 1200°C.